INCREASE EFFICIENCY WITH PRODUCTION MODEL RE-LEYOUT USING ACTIVITY RELATIONSHIP CHART - Ari Prayogo; Hasmand Zusi (Dinasti International Journal of Education Management And Social Science, 2020)
This thesis contains an analysis to increase efficiency with production model re-layout using activity relationship chart. The research already done at manufacturing making wiring harness located in Balaraja, Tangerang with model carline Toyota Hiace. Based on existing layout, writer defines 21 facilities from beginning process (Pre-Assy) until end process (Inspection). For decide degrees of closeness, writer and stakeholder for the company do brainstorming to formulate 7 criteria for relevance motive table. Based 7 criteria, 21 each facilities can be decided degrees of closeness and mapped out in activity relationship chart. Degrees of closeness each facility can be divided into 6 levels as A (Absolute), E (Especially), I (Important), O (Ordinary), U (Unimportant), and X (Undesirable). Information of degree of closeness become a basis for making new layout more efficiency by using block tamplate but should be adjusted based on layout type production system. Type of layout that suitable is layout by product with improve efficiency from 63% to 65%.